Development of Electric Propulsion Technology in Aviation - Lingyun Shao; Zhuoran Zhang; Huamin Gao; Weikang Huang; Han Xue; Yue Xu (中国工程科学)
The electric propulsion of aircraft has triggered a new wave of innovation and reform in the aviation sector. It is considered as an important move to implementing green development in aviation and addressing global environmental challenges. This study examines the research progress of the electric propulsion technology in aviation and reveals the technology gap between China and other countries, clarifying the technology challenges for developing electric aircraft in China. Four key technologies regarding electric propulsion in aviation are identified: long-life and high-energy-density batteries, electric propulsion with high efficiency and a high power-to-weight ratio, integrated management of energy, and aerodynamic configuration with a high lift-to-drag ratio. The industry characteristics and research status of the above technologies are investigated, and their future directions as well as the fundamental technical problems are clarified. Based on a performance evaluation model for electric aircraft, the influence of key technical parameters on the performance of electric aircraft are analyzed; these parameters include energy density of batteries, power-to-weight ratio and efficiency of motors, and lift-to-drag ratio of aircraft. Besides, the practicability of applying full electric propulsion on aircraft for urban air transport, commuter transport, and regional use are evaluated. By cconsidering the current status and future development of key components such as high-energy-density storage batteries and high-performance propulsion systems, China should leverage its technological accumulation in the renewable energy industry and its advanced industrial foundation to establish a strategic plan for the development of electric aircraft oriented at urban air transport, commuter transport, and regional use, gradually extending the application of electric propulsion in civil aviation.